Application of intravascular physiology methods in clinical practice: two-year data from the Russian registry - V. V. Demin; A. M. Babunashvili; T. V. Kislukhin; E. Yu. Kostyrin; Z. Kh. Shugushev; V. N. Ardeev; E. V. Merkulov; Yu. G. Matchin; E. Yu. Gubarenko; N. A. Kochergin; S. P. Semitko; A. A. Anufriev; et al. (Российский кардиологический журнал)
Aim. To analyze the use in clinical practice of intravascular coronary assessment methods based on two-year data from the Russian Registry on the Use of Intravascular Imaging and Physiology.Material and methods. Since 2021, the Russian Registry on the Use of Intravascular Imaging and Physiology has included data from 7967 studies in 3932 patients, of which 3086 (38,7%) were studies of intravascular physiology. In 2021, 13 branches from 9 cities participated in the registry, in 2022 — 20 branches from 11 cities. For chronic coronary artery disease, 2484 (80,5%) studies were performed, for acute coronary syndrome (ACS) — 598 (19,4%).Results. In 2022, the registry included 1,9 times more intravascular functional studies compared to 2021. The contribution of different clinics was uneven — 75,7% of studies were performed in three departments. The use of non-hyperemic indexes prevailed over hyperemic ones (58%), and in ACS they were used three times more often. All coronary arteries were examined, most often the anterior descending artery. As a primary diagnosis, 1968 (63,8%) studies were performed, while for the purpose of dynamic control — 122 (3,9%), at the surgical stage — 996 (32,3%). In 85,5% (n=2638) of observations, the functional assessment of stenosis hemodynamic significance directly influenced the treatment tactics.Conclusion. The registry data indicate the significant role of functional methods among intravascular diagnostic options in the practice of domestic clinics participating in the registry. The registry demonstrated their use as a primary diagnosis 2 times more often than for coronary artery stenting. Some indications for the active use of intravascular physiology methods (in acute coronary syndrome, left coronary artery involvement) are currently controversial and require further research.